2014
DOI: 10.1111/jon.12182
|View full text |Cite
|
Sign up to set email alerts
|

Brain Atrophy in Radiologically Isolated Syndromes

Abstract: NTBV and NCV were significantly lower in RIS compared with ISC while no differences were observed in NWMV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 15 publications
3
34
1
1
Order By: Relevance
“…31 Lower baseline brain volumes found in this study can reflect more aggressive disease ongoing even before the first clinical manifestation. 32 The results from this study indicate that the association between accumulation of new/enlarging T2 lesions and development of whole-brain atrophy and enlargement of lateral ventricles was stronger than the association with the GM volume measures. The close association between lateral ventricular enlargement and accumulation of T2 lesions in patients with CIS was previously reported.…”
Section: Discussionmentioning
confidence: 74%
“…31 Lower baseline brain volumes found in this study can reflect more aggressive disease ongoing even before the first clinical manifestation. 32 The results from this study indicate that the association between accumulation of new/enlarging T2 lesions and development of whole-brain atrophy and enlargement of lateral ventricles was stronger than the association with the GM volume measures. The close association between lateral ventricular enlargement and accumulation of T2 lesions in patients with CIS was previously reported.…”
Section: Discussionmentioning
confidence: 74%
“…Although these results were somewhat unexpected, they are indeed in line with previous research. Thus, although a large number of studies did not find decreased whole brain and cortical volumes in CIS patients, 36,37,39,4345 all the studies published so far (with the exception of one publication) 10 have reported total brain and cortical atrophy in RIS patients, 3,6,8,9,12 thereby suggesting that, in contrast to CIS patients, decreased cortical volume in RIS patients is highly consistent. However, there are also several reasons that might partially explain these results: CIS patients had a lower median white matter lesion volume compared with RIS (albeit not significant); although there was no significant age difference among CIS and RIS groups in the present study, RIS patients were approximately 2 years older than those from the CIS group; nearly one-third of the CIS patients presented with spinal cord symptoms, which might led to lower average cortical thickness (the type of clinical picture at onset has been found to correlate with atrophy in the corresponding cortical areas) 46 ; in contrast with MS and CIS patients, the absence of a definable clinical event makes it impossible to establish the disease evolution among RIS patients and, thus, there is the possibility that RIS evolution have actually a much longer duration than expected.…”
Section: Discussionmentioning
confidence: 91%
“…The cerebral gray matter (GM) develops atrophy throughout the MS disease course, both very early [15] and as the disease continues to advanced stages [16]. GM and white matter (WM) pathology are not necessarily closely coupled [15].…”
Section: Original Articlementioning
confidence: 99%
“…The cerebral gray matter (GM) develops atrophy throughout the MS disease course, both very early [15] and as the disease continues to advanced stages [16]. GM and white matter (WM) pathology are not necessarily closely coupled [15]. Furthermore, previous studies have shown that the deep gray matter (DGM, i.e., basal ganglia and thalamus) is disproportionately affected as compared to the cortical GM [17] and whole brain [18,19] and such involvement is highly clinically relevant [19][20][21][22].…”
Section: Original Articlementioning
confidence: 99%